Photoinduced damage of AsLOV2 domain is accompanied by increased singlet oxygen production due to flavin dissociation - Petrenčáková, Martina; Filandr, František; Hovan, Andrej; Yassaghi, Ghazaleh; Man, Petr; Kožár, Tibor; Schwer, Marc-Simon; Jancura, Daniel; Plückthun, Andreas; Novák, Petr; Miškovský, Pavol; Bánó, Gregor; et al. (Scientific reports, 2020)
Flavin mononucleotide (FMN) belongs to the group of very efficient endogenous photosensitizers producing singlet oxygen, 1O2, but with limited ability to be targeted. On the other hand, in genetically-encoded photosensitizers, which can be targeted by means of various tags, the efficiency of FMN to produce 1O2 is significantly diminished due to its interactions with surrounding amino acid residues. Recently, an increase of 1O2 production yield by FMN buried in a protein matrix was achieved by a decrease of quenching of the cofactor excited states by weakening of the protein-FMN interactions while still forming a complex. Here, we suggest an alternative approach which relies on the blue light irradiation-induced dissociation of FMN to solvent. This dissociation unlocks the full capacity of FMN as 1O2 producer. Our suggestion is based on the study of an irradiation effect on two variants of the LOV2 domain from Avena sativa; wild type, AsLOV2 wt, and the variant with a replaced cysteine residue, AsLOV2 C450A. We detected irradiation-induced conformational changes as well as oxidation of several amino acids in both AsLOV2 variants. Detailed analysis of these observations indicates that irradiation-induced increase in 1O2 production is caused by a release of FMN from the protein. Moreover, an increased FMN dissociation from AsLOV2 wt in comparison with AsLOV2 C450A points to a role of C450 oxidation in repelling the cofactor from the protein.